Evidence-Based Benchmarking Framework for a Distributed Leadership Approach to Capacity Building in Learning and Teaching : Final Report. - Jones, Sandra; Hadgraft, Roger; Harvey, Marina; Lefoe, Geraldine; Ryland, Kevin (Office for Learning and Teaching, 2014)
Final report from a project that has as its focus ALTC Leadership Priority One: institutional leadership to enhance learning and teaching (L&T) through leadership capacity-building at the institutional level. The intent was to develop a systematic, evidence-based benchmarking framework for Distributed Leadership (DL) to build leadership capacity in learning and teaching (L&T). The project used the principles and practices identified in the Action Self Enabling Reflection Tool for DL (developed from project LE9- 1222) to undertake the initial desk audit of ALTC projects funded as DL and disciplinary and cross-disciplinary projects and to provide questions for a national survey of existing practice using DL to build leadership capacity. A Community of Practice (CoP) was established as part of the project to network developments, evaluate findings and monitor developments. The evidence-based benchmarking framework was developed and designed as a web-based interactive tool to facilitate benchmarking across the sector.